Altered Level of Consciousness in Metabolic Disease: An Emphasis on the Pathomechanism of Hepatic Encephalopathy - Steven Jonathan; I Ketut Suryana; I Made Suma Wirawan (International Journal of Health and Pharmaceutical (IJHP), 2026)
Altered level of consciousness (ALOC) is a common clinical presentation in emergency and inpatient settings, with metabolic diseases representing as major etiologic causes. Among these, hepatic encephalopathy (HE) is one of the most frequent causes due to its high prevalence, morbidity, and mortality. HE has a complex pathophysiology mechanism involving neurotoxic substances such as ammonia. This narrative literature review discusses ALOC associated with metabolic disease, with emphasis on the underlying pathophysiological mechanisms of HE. Metabolic encephalopathy arises from systemic disturbances rather than primary structural brain injury and may progress to irreversible neuronal damage if untreated. HE develops in the context of acute liver failure, portosystemic shunting, or cirrhosis. Its pathogenesis reflects a multifactorial interaction involving hyperammonemia, systemic inflammation, gut microbiome dysbiosis, electrolyte disorders, malnutrition, sarcopenia, and manganese accumulation. Ammonia remains a central neurotoxin in HE, contributing to astrocytic swelling, glutamine accumulation, and cytotoxic edema. Inflammatory response further neuronal impairment through cytokine-mediated oxidative stress and blood–brain barrier disruption. Gut dysbiosis promotes bacterial translocation and endotoxemia, exacerbating systemic inflammation and worsening neurocognitive impairment. Given the broad differential diagnosis of ALOC, a structured clinical approach and early identification of metabolic causes especially HE is essential. Understanding the complex